Millimeter-Scale and Large-Angle Self-Collimation in a Photonic Crystal Composed of Silicon Nanorods - Hao Li (IEEE Photonics Journal, 2013)
We report the observation of a large-angle self-collimation phenomenon occurring in photonic crystals (PCs) composed of nanorods. Electromagnetic waves incident onto such PCs from directions covering a wide range of incident angles become highly localized along a single array of rods, which results in the narrow-beam propagation without divergence. A propagation length of 0.4 mm is experimentally observed over the wavelength ranging from 1540 nm to 1570 nm even in the large incident angle case, which is a very considerable length scale for on-chip optical interconnection.